Tensile strength evaluation on burns wound healing treated with nenas (Ananas comosus spp.) and gelam (Melaleuca spp.) honey - Mohd Zohdi, Rozaini; Abu Bakar @ Zakaria, Md Zuki; Mohamed Mustapha, Noordin; Yusof, Norimah; Abdullah, Muhammad Nazrul Hakim (Universiti Putra Malaysia Press, 2004)
The influence of Malaysian honey on biomechanical properties of burn wound was assessed by creating a deep partial skin thickness burn on the dorsal part of Sprague-Dawley. A total of 45 Sprague Dawley male rats weighing 200-300 g were used in this study. Two types of local honeys (nenas and gelam) were applied twice a day in a quantity of 0.5 ml for each application, while control animals received no treatment. The rats were serially euthanatized at 3, 7, 14, 21 and 28 days post treatment for tensile strength study. Tensile strength test showed progressed increased in wound tensile strength of all experimental groups. There is no significant difference between the groups but nenas-treated group showed the highest value of tensile strength at day 3, 14, 21 and 28 day post injury. This study showed that there was an acceleration of the dermal repair in wound healing treated with Nenas honey compared to control and honey Gelam-treated groups as characterized by an increase in tensile strength.